USSR Report, Earth Sciences. - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1987)
Partial Contents: Meteorology, Geography, Oceanography, Temperature Conditions, Ecological and Geographical Problems, Oceanographic Method, Volcanic Depression, Geothermal Field, Electromagnetic Induction, Terrestrial Geophysics, Electroenergetic Seismic, Earthquake, Geochemical,Physics of Atmosphere, Electromagnetic Radiation, Arctic and Antarctic research.